Amorphous silicoboron carbonitride monoliths resistant to flowing air up to 1800 °C. (August 2016) - Liang, Bin; Yang, Zhi-Hua; Jia, De-Chang; Rao, Jian-Cun; Yu, Dong-Li; Tian, Yong-Jun; Li, Quan; Miao, Yang; Zhu, Qi-Shuai; Zhou, Yu
Graphical abstract: TEM images showing the microstructure and morphologies of a cross section of oxidized SiBCN ceramic sample at 1700 °C for 8 h. (a) BF image showing the morphologies on the cross section; (b)–(d) BF images at high magnification corresponding to the zones marked by boxes B, C and D in (a), respectively; (e) SAED pattern corresponding to the zones marked by the circle E in (a); (f)–(g) HRTEM images corresponding to the zone marked by the circle F&G in (a); (h) linear scanning result showing the element distribution along the red line H in (a). This figure is identical to Fig. 10 in the newly submitted manuscript. It shows the microstructure and morphologies of a cross section of oxidized SiBCN ceramic sample at 1700 °C for 8 h in flowing air. The monolith retains significant resistance to oxidation at temperatures up to 1800 °C. The formation of dense, passivating surface layers of N-rich amorphous SiO2 coupled with the ternary chemical bonds (CBN and BCN) and capsule-like structures are primarily responsible for the excellent oxidation resistance. The figure is therefore considered to be very representative highlight. Highlights: Oxidation resistance of dense, amorphous SiBCN monoliths was studied. They exhibit a better oxidation resistance than SiC and Si3 N4 above 1600 °C. They are well resistant to oxidation at temperatures up to 1800 °C in flowing air. Abstract: The oxidation resistance of amorphous SiBCN monolith was investigated at 1500–1800 °C. The oxide products are amorphous SiO2 and cristobalite underlying amorphous oxide scale. The release of gases including CO, CO2, N2 and evaporation of B2 O3 result in formation of bubbles and loose, porous oxide scale at 1600 °C. SiBCN monolith exhibits oxidation resistance superior to SiC and Si3 N4 above 1600 °C, and retains significant resistance to oxidation up to 1800 °C. The formation of dense, passivating surface layers of N-containing amorphous SiO2, the ternary chemical bonds and capsule-like structures are primarily responsible for the oxidation resistance.